IMPLEMENTASI NILAI-NILAI PANCA JIWA PONDOK MODERN DAN KONTRIBUSINYA DALAM PEMBENTUKAN KEMANDIRIAN USAHA PRODUKTIF SANTRI - naesih, Nur; Syarifudin, Encep; Hunainah, Hunainah; Wasehudin, Wasehudin; Lazzavietamsi, Fandy Adpen (PARAMUROBI: JURNAL PENDIDIKAN AGAMA ISLAM, 2024)
Islamic boarding school is an Islamic educational institution with a dormitory system, which is considered to have a conducive learning environment to shape the character and application of Islamic teaching values to students in their daily lives. One of the values applied in Islamic boarding schools is the five souls, namely the spirit of the boarding school which is the foundation and guide for behavior. However, with the rapid development of the times and science and technology, many problems and errors in thinking patterns have emerged regarding the education provided by Islamic boarding schools, including the Al-Hasyimiyah Modern Islamic Boarding School. Therefore, this research aims to analyze in more depth the implementation of the five soul values of modern Islamic boarding schools to shape the character of the students of Al-Hasyimiyah modern Islamic boarding school. In its implementation, the researcher used a qualitative case study type method, which used primary data sources obtained from participant observation, interviews and documentation. The results of the study show that the five souls implemented by the Al-Hasyimiyah Modern Islamic Boarding School are sincerity, simplicity, independence, Islamic brotherhood, and freedom. The implementation of the five souls of modern Islamic boarding school is to form the independence of the students' productive economic efforts of class 6 KMI students at the Al-Hasyimiyah Modern Islamic Boarding School through daily activities at the Islamic boarding school and the example of the religious teachers. These activities are actualized in the form of daily to annual activity programs.